Undue Delegation: Private Delegation and Other Strategies to Challenge Admitting-Privileges Laws - Ma, Jacqueline Y. (Columbia Journal of Gender and Law, 2015)
In November 2015, the Supreme Court granted certiorari to Whole Woman’s Health v. Cole,1 the first reproductive rights case to reach the court since Gonzales v. Carhart2eight years before. In the intervening time, states have passed an astonishing number of laws and regulations that encroach on women’s access to abortion. Many such laws ostensibly aim to protect the woman and her fetus. Yet these same laws do so by imposing medically unnecessary and onerous procedural requirements on women,3which can erect massive barriers to abortion access for individuals. Other state laws aim to regulate not the activities of women, but those of abortion providers, who are not a protected class. The reproductive rights movement terms these laws Targeted Regulations of Abortion Providers, or TRAP laws. 4 State legislatures’ passage of TRAP laws accelerated after the Supreme Court’s decision in Carhart, which was taken to signal judicial willingness to uphold state laws that aim to protect an unborn fetus at the expense of reducing a woman’s ability to choose.5 This Note focuses on admitting-privileges laws, a type of TRAP law that requires physicians who provide abortions to obtain staff privileges at a hospital within a certain distance from their clinics. Without these required privileges, physicians performing abortions risk civil and criminal penalties. These laws are especially concerning because they give area hospitals an effective veto over a clinic’s operations, effectively outsourcing the power to deny licenses to private entities. Admitting-privileges decisions are often discretionary for hospital administrators; a hospital’s denial of admitting privileges also lacks state oversight or external appeals. Admitting-privileges laws are being ratified throughout many states, but have proven resistant to traditional substantive due process challenges. In addition to traditional “undue burden” analysis, a multipronged approach to reproductive rights litigation and advocacy is necessary. Part I of this Note sets forth a brief history of the right to choose an abortion and the current federal legal framework. Then, it details recent state legislative and ballot initiatives aimed at regulating abortion providers. Part II explains the complications of using the “undue burden” doctrine in constitutional challenges to state action, as illuminated by recent cases litigating admitting-privileges laws. It further introduces private-delegation challenges as an alternative method to examine the constitutionality of these laws. Part III looks at the history of private-delegation challenges with respect to admitting-privileges laws and touches on other possible avenues to challenge admitting-privileges regulations.